Increasing Question Quality of Student through Problem Based Learning at Grade X MIA 6 of SMA N 4 Surakarta - Atika Guritna Ayu; Sri Widoretno; Slamet Santosa; Murni Ramli; Joko Ariyanto (Universitas Sebelas Maret, 2015)
The research aims to increase the qualities of student’s question through problem based learning at Grade X MIA 6 of SMA N 4 Surakarta. The research was a four-cycle action research conducted in academic year 2014/2015. Data were collected through observation, interview and video recording. All question were categorized based on revised Bloom Taxonomy. Data were validated using triangulation method. The result of the research showed that: 1) problem based learning effectively increase the quality of student’s question. The distribution of the lower order thinking question (C1-C2) decreased each cycle, however the higher order thinking question (C4-C5) increased. 2) the quantity of student’s question was dominated by C2 question (40,91%) at the first cycle, and the majority was C3 type question (24,65%) at the second cycle, and at the third and fourth cycle, C4 question was the most (25,86% and 27,83%).Keywords: qualities of student’s question, problem based learning